2014
DOI: 10.1074/jbc.m113.489336
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 2 Compensates for Desmoglein 3 but Does Not Control Cell Adhesion via Regulation of p38 Mitogen-activated Protein Kinase in Keratinocytes

Abstract: Background:The roles of the adhesion molecules desmoglein (Dsg) 2 and Dsg3 for keratinocyte adhesion and signaling are poorly understood. Results: Dsg2 compensates for Dsg3 depletion with regard to cell cohesion, but, in contrast to Dsg3, does not regulate p38 MAPK signaling. Conclusion: Dsg2 and Dsg3 contribute differently to cell adhesion and signaling pathways.Significance: The results demonstrate unique functions of different Dsgs expressed in the same cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 42 publications
12
46
1
11
Order By: Relevance
“…2a). In accordance with our previous findings [25], depletion of Dsg3 led to 1.5-fold p38 MAPK activation compared to non-targeting (n.t.) siRNA controls.…”
Section: E-cadherin Compensates For Effects Of Desmosomal Perturbationsupporting
confidence: 80%
See 2 more Smart Citations
“…2a). In accordance with our previous findings [25], depletion of Dsg3 led to 1.5-fold p38 MAPK activation compared to non-targeting (n.t.) siRNA controls.…”
Section: E-cadherin Compensates For Effects Of Desmosomal Perturbationsupporting
confidence: 80%
“…Dissociation assays showed that 24 h incubation with Decma-1 at high (12.5 lg/ml) as well as low (2.5 lg/ml) doses resulted in loss of cell cohesion (number of fragments per well: 16 ± 2 and 7 ± 1) compared to control cells (1 ± 1). Similar to the situation of impaired Dsg3 binding as previously published [7,25], co-incubation with the p38 MAPK inhibitor SB202190 significantly reduced the number of fragments (12.5 lg/ml Decma-1: 10 ± 2 and 2.5 lg/ml Decma-1: 4 ± 1) (Fig. 1d).…”
Section: E-cadherin Compensates For Effects Of Desmosomal Perturbationsupporting
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, Dsg2 expression was visible which is different from human epidermis, where Dsg2 could be found in hair follicles only. 15 Specific Dsc1 staining was absent. The desmosomal plaque proteins plakoglobin (PG) and desmoplakin (DP) were uniformly expressed throughout all layers (Figs.…”
Section: Characterization Of the Expression Pattern Of Desmosomal Molmentioning
confidence: 99%
“…Genotyping of progeny of heterozygous B6; 129X1-Dsg3 tm1Stan / J mice (Jackson Laboratory, Bar Harbor, ME, USA) 14 was performed as described previously 15 and PCR analyses were done after a well-established protocol. 16 Homozygous Dsg3 À/À animals), the animal and a WT littermate were euthanized and eyes together with eyelids were enucleated as described previously.…”
Section: Dsg3 Mice -Genotyping and Enucleation Of Whole Eyesmentioning
confidence: 99%